Fooling the eye: trompe l’oeil porcelain in High Qing China - Chih-en Chen (Les Cahiers de Framespa)
Porcelain imitation of other materials, or so-called ‘trompe l'oeil’ porcelain, popular from the late Yongzheng to the Qianlong period, has been regarded as an aesthetic representative of Chinese emperors as well as an iconography of court power. Several studies have been conducted to understand the connection between porcelain and emperors’ connoisseurship; however, much of that research has focused on the physical characteristics of porcelain and corresponding imageries, namely the painted antiquity cataloging album. Such object-focused methodology overlooks the concept underlying the works, which is inherently related to their very existence, namely their origin. Pierson characterizes this traditional approach as ‘outward focused’, and suggests a new methodology to overcome its shortcomings. This framework is focused on ‘of the period’ literatures, to define the understanding of certain aesthetics. Therefore, in this essay, numerous Chinese classics are reviewed from Warring States period Lilun to Qing dynasty Hong Lou Meng. Following the terminology investigation over Chinese classic literatures, this research proposes some possible rationale behind a considerable number of trompe l'oeil porcelains passed down from the Qing Imperial workshops which seems to be ignored in Huoji dang. Moreover, based on Huoji dang, this essay aims to understand how Qing dynasty emperors and the Imperial workshop’s reception of trompe l'oeil works of art and their iconographic connotations.